Cardiac sympathetic dysfunction in the prehypertensive spontaneously hypertensive rat - Shanks, J; Herring, N; Manou-Stathopoulou, S; Lu, C; Li, D; Paterson, D (American Physiological Society, 2013)
Recent studies in prehypertensive spontaneously hypertensive rats (SHR) have shown larger calcium transients and reduced norepinephrine transporter (NET) activity in cultured stellate neurons compared with Wistar-Kyoto (WKY) controls, although the functional significance of these results is unknown. We hypothesized that peripheral sympathetic responsiveness in the SHR at 4 wk of age would be exaggerated compared with the WKY. In vivo arterial pressure (under 2% isoflurane) was similar in SHRs (88 ± 2/50 ± 3 mmHg, n = 18) compared with WKYs (88 ± 3/49 ± 4 mmHg, n = 20). However, a small but significant (P < 0.05) tachycardia was observed in the young SHR despite the heart rate response to vagus stimulation (3 and 5 Hz) in vivo being similar (SHR: n = 12, WKY: n = 10). In isolated atrial preparations there was a significantly greater tachycardia during right stellate stimulation (5 and 7 Hz) in SHRs (n = 19) compared with WKYs (n = 16) but not in response to exogenous NE (0.025–5 μM, SHR: n = 10, WKY: n = 10). There was also a significantly greater release of [3H]NE to field stimulation (5 Hz) of atria in the SHR (SHR: n = 17, WKY: n = 16). Additionally, plasma levels of neuropeptide Y sampled from the right atria in vivo were also higher in the SHR (ELISA, n = 12 for both groups). The difference in [3H]NE release between SHR and WKY could be normalized by the NET inhibitor desipramine (1 μM, SHR: n = 10, WKY: n = 8) but not the α2-receptor antagonist yohimbine (1 μM, SHR: n = 7, WKY: n = 8). Increased cardiac sympathetic neurotransmission driven by larger neuronal calcium transients and reduced NE reuptake translates into enhanced cardiac sympathetic responsiveness at the end organ in prehypertensive SHRs.